DESIGN AND IMPLEMENTATION OF FLASHCARD-BASED GAME LEARNING MEDIA FOR ELEMENTARY SCHOOL MATHEMATICS - Nur Chasanah; Joko Sulianto; Joko Siswanto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to design and implement Flashcard-based Game-Based Learning (GBL) media to enhance elementary students’ understanding of basic arithmetic operations. The research followed the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages. The product’s feasibility was assessed through expert validation, practicality testing, and effectiveness evaluation. The results show that the Flashcard-based GBL media achieved an average validation score of 3.89 (very feasible) in terms of content, design, and language suitability. The practicality test obtained scores ranging from 3.95 to 4.00, indicating that the media was easy to use and engaging for both teachers and students. Effectiveness testing revealed a significant improvement in students’ learning outcomes, with mean scores increasing from 49.63 (pretest) to 78.83 (posttest), an N-Gain of 0.60, and a p-value < 0.05. These findings demonstrate that Flashcard-based GBL effectively improves mathematical understanding, motivation, and learning engagement in a fun and interactive environment.